Determinants of Early Financial Reporting in Indonesia’s Financial Sector: The Role of RegTech and Institutional Type - Lubis, M. Daffa Fahada; Putri, Andi Qur'ani Ratu Sabrina Arham (Journal of Economics, Social, and Humanities, 2026)
This study examines the drivers of early financial reporting across Indonesia’s financial institutions. It highlights the influence of institutional type and technological adoption. While digital tools like RegTech are often promoted as solutions for timely compliance, our findings reveal that institutional characteristics, particularly being a financing institution, are far more decisive. Entities in the financing sector, not finance sector as a whole, are over 30 times more likely to report early with a probability increase of more than 50 percentage points compared to other sectors. In contrast, factors such as RegTech adoption, firm size, and IT infrastructure do not exhibit significant influence on reporting timeliness. These results suggest that organizational alignment with regulatory expectations and internal governance practices play a more critical role than digital maturity alone. Despite high levels of technology adoption, early reporting behavior remains uneven which shows reinforcing the notion that technology is not a standalone solution. The logistic regression model used in this study demonstrates strong predictive ability which emphasizes the importance of sectoral identity in shaping reporting outcomes. Policymakers are encouraged to move beyond one-size-fits-all digital mandates and instead develop targeted strategies that address the specific institutional contexts of financial entities